A queer theory of software studies: software theories, queer studies. Issue 11 (2nd November 2017) - Cockayne, Daniel G.; Richardson, Lizzie
Abstract: This introduction to the themed section 'Queering Code/Space' poses the question: what is the spatial relationship between technology and sexuality? We outline two overarching issues concerning technology and sexuality that lie outside of yet intersect with discussions in geographical scholarship. We then detail the characteristics of two largely distinct schools of thought – software studies and queer theory – to examine the tensions of and correspondence between these separate intellectual systems. We assess what might be productively found at the intersections of software studies and queer theory in terms of their respective epistemological approaches toward the topics of technology and sexuality. We briefly outline the effects the combination of software studies and queer theory have had on geography and what more they might have to offer. We conclude by providing an overview of the articles in the themed section.